Interview: Professional autonomy in primary healthcare: A dream come true by francine campolim - Senna Pierri, Maria Eduarda [UNESP]; Duarte Moreira, Raquel Regina [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
In this interview, Francine Campolim talks about the experience of implementing phytotherapy in Itapeva/SP in collaboration with a local cooperative.
A autonomia do profissional dentro do processo de cuidado na Atenção Primária: Um sonho realizado por Francine Campolim
Keywords: Health System; Herbal medicine; Medicinal plants